“Sin las ollas, no hubiéramos sobrevivido”: Estado de la cuestión de la problemática social de las ollas comunes durante la pandemia del COVID-19 - Montoya Díaz, Raúl Humberto (Pontificia Universidad Católica del Perú, 2024)
The “ollas comunes” (CO) (“common pots”) have played an important role as essential food organizations over the past four years during the COVID-19 pandemic, serving as the primary food sources for numerous families facing difficulties during this period. The objective of this paper is to present an introductory context on the role of common pots during the pandemic. Following this, a brief overview of the state of the issue concerning community kitchens and common pots in Peru and Latin America will be presented. The methodology used in this paper was a literature review, analyzing previous research on these food organizations.

Las ollas comunes (OC) han desempeñado un papel importante como organizaciones alimentarias esenciales en los últimos cuatros años durante el contexto de la pandemia del COVID-19, ya que son las principales fuentes de alimentación para numerosas familias que enfrentaron dificultades durante este periodo. El objetivo de este trabajo es presentar un contexto introductorio sobre el rol de las OC durante la pandemia. Luego, se presentará un breve estado de la cuestión acerca de los comedores populares (CP) y las OC en Perú y Latinoamérica. La metodología utilizada en este trabajo fue la revisión bibliográfica, puesto que se analizaron investigaciones previas sobre estas organizaciones alimentarias.
We would not have survived without the Ollas: State of the Art of the Social Problematic of ollas comunes during the COVID-19 Pandemic
Keywords: Food organizations; Economic crisis; Food security; Urban areas; Common pots; COVID-19; Organizaciones alimentarias; Crisis económica; Seguridad alimentaria; Zonas urbanas; Ollas comunes; COVID-19; https://purl.org/pe-repo/ocde/ford#5.04.03